DDT Jazzband institution and legend: 50 years - DDT Jazzband; Andersson, Fred; Mesimäki, Pekka; Mutikainen, Pentti; Nyman, Carl Gustav; Näätänen, Raimo; Oiling, Matti; Peltoniemi, Timo; Rönnholm, Thomas; Sandell, Christer; Sarpila, Antti; Schwindt, Christian; et al. (DDT Jazzband, 2008)
16 kappaletta.